2012
DOI: 10.1590/s0100-55022012000300016
|View full text |Cite
|
Sign up to set email alerts
|

PET-Saúde: (in)formar e fazer como processo de aprendizagem em serviços de saúde

Abstract: -Educação em Saúde; -Aprendizagem. RESUMO As novas diretrizes curriculares dos cursos da área da saúde enfatizam a inserção precoce e responsável

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0
14

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
4
0
14
Order By: Relevance
“…This significant learning occurs in this context from the time the PET-Saúde provides the contact of the students with the services and the territory of a community. This result corroborates the findings of other authors who have studied the participation of students in PET-Saúde 4,[6][7][8][9][20][21][22][23] . It is noteworthy that, in this perspective, it is important to be assigned a meaning to this approach of future health professionals with the people, not being relevant only to enter on the practice field in a single and isolated manner.…”
Section: Recognition Of the Health Needssupporting
confidence: 92%
See 2 more Smart Citations
“…This significant learning occurs in this context from the time the PET-Saúde provides the contact of the students with the services and the territory of a community. This result corroborates the findings of other authors who have studied the participation of students in PET-Saúde 4,[6][7][8][9][20][21][22][23] . It is noteworthy that, in this perspective, it is important to be assigned a meaning to this approach of future health professionals with the people, not being relevant only to enter on the practice field in a single and isolated manner.…”
Section: Recognition Of the Health Needssupporting
confidence: 92%
“…As the result obtained in this study, other authors also identified as one of the limitations of PET-Saúde the incompatibility of schedules for carrying out practices or tutorial meetings 5,8,9 . This factor is directly related to the different time courses of the institution, as well as curricular inflexibility, since the obligation to comply with the semiannual components of high workload provides few spaces for the development of activities not covered in the curriculum.…”
Section: Incompatibility Of Schedulessupporting
confidence: 56%
See 1 more Smart Citation
“…Percebe-se a visão que o estudante tem em colocar em prática o conhecimento, pois há uma série de dificuldades enfrentadas no decorrer do curso como limitação dos recursos oferecidos pelas faculdades, desvalorização quanto ao tema, falta de interesse da própria população e falta de motivação dos tutores de forma clara. Observa-se a prática como obrigação enquanto acadêmico apenas para sua futura formação (17) . Os estudantes são desafiados nos primeiros contatos com a educação em saúde, pois as práticas educativas são tarefas difíceis e requerem preparação mais aprofundada dos saberes em saúde, e a construção é dada através de cada período até sua formação.…”
Section: Satisfação Na Experiência Prática De Educação Em Saúde: Exerunclassified
“…O pensamento crítico sobre conceito saúde-doença foi intensificado, entrando em pauta a necessidade de mudança na formação de profissionais de saúde, visto que a lei regulamentadora do SUS visa à formação de profissionais com o perfil adequado ao mesmo. Neste momento entrou em pauta a importância da inserção de acadêmicos em projetos que visem à integralização entre ensino, serviço e comunidade, valorizando a interdisplinaridade e troca de saberes 6,7 . A Tabela 1 apresenta a participação em atividades voluntárias extracurriculares durante a graduação, o que não demonstrou significância estatística sobre os grupos estudados.…”
unclassified